Mindfulness Training to Reduce Ego Depletion in College Students: A Quasi Experimental Study - Agustin, Erina Dwi; Agustin, RIzky Melania; Izzati, Dewi Sakhsiyatul; Salsabila, Alfa Nadya Nisma; Ananda, Dimas Firman; Wahyuni, Endang; Suryani, Suryani (International Conference on Sustainable Health Promotion, 2023)
Ego depletion is a condition where individuals experience a setback in self-control and daily activities. The aim of the intervention was to determine the effectiveness of mindfulness training in reducing ego depletion in 6th semester students. There were 60 participants divided into the experimental group (N=30) and the control group (N=30). Mindfulness training in this study consisted of five sessions. The design of the study was an untreated control group design with dependent pretest and posttest samples. Data analysis used descriptive statistical techniques with quantitative and qualitative tables. The ego depletion research instrument uses an adaptation scale totaling 15 items of physical, mental and emotional exhaustion. The results showed that there were significant differences in the experimental group and the control group. This proves that mindfulness is proven to reduce student ego depletion